Mechanisms underlying prelimbic prefrontal cortex mGlu3/mGlu5-dependent plasticity and reversal learning deficits following acute stress. (January 2019) - Joffe, Max E.; Santiago, Chiaki I.; Stansley, Branden J.; Maksymetz, James; Gogliotti, Rocco G.; Engers, Julie L.; Nicoletti, Ferdinando; Lindsley, Craig W.; Conn, P. Jeffrey
Abstract: Stress can precipitate or worsen symptoms of many psychiatric illnesses. Dysregulation of the prefrontal cortex (PFC) glutamate system may underlie these disruptions and restoring PFC glutamate signaling has emerged as a promising avenue for the treatment of stress disorders. Recently, we demonstrated that activation of metabotropic glutamate receptor subtype 3 (mGlu3 ) induces a postsynaptic form of long-term depression (LTD) that is dependent on the activity of another subtype, mGlu5 . Stress exposure disrupted this plasticity, but the underlying signaling mechanisms and involvement in higher-order cognition have not yet been investigated. Acute stress was applied by 20-min restraint and early reversal learning was evaluated in an operant-based food-seeking task. We employed whole-cell patch-clamp recordings of layer 5 prelimbic (PL)-PFC pyramidal cells to examine mGlu3 -LTD and several mechanistically distinct mGlu5 -dependent functions. Acute stress impaired both mGlu3 -LTD and early reversal learning. Interestingly, potentiating mGlu5 signaling with the mGlu5 positive allosteric modulator (PAM) VU0409551 rescued stress-induced deficits in both mGlu3 -LTD and reversal learning. Other aspects of PL-PFC mGlu5 function were not disrupted following stress; however, signaling downstream of mGlu5 -Homer interactions, phosphoinositide-3-kinase (PI3K), Akt, and glycogen synthase kinase 3β was implicated in these phenomena. These findings demonstrate that acute stress disrupts early reversal learning and PL-PFC-dependent synaptic plasticity and that potentiating mGlu5 function can restore these impairments. These findings provide a framework through which modulating coordinated mGlu3 /mGlu5 signaling may confer benefits for the treatment of stress-related psychiatric disorders. Highlights: PL-PFC mGlu3 /mGlu5 -LTD requires PI3K-Akt signaling, and not Ca 2+ mobilization. Acute stress disrupts mGlu3 /mGlu5 -LTD without a gross impairment to mGlu5 function. Potentiating mGlu5 rescues LTD deficit following acute restraint stress. Potentiating mGlu5 ameliorates reversal learning deficit following acute stress.